2001
DOI: 10.1074/jbc.m108893200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cell Migration and Disruption of the Actin Cytoskeleton in Calpain-deficient Embryonic Fibroblasts

Abstract: The physiological functions and substrates of the calcium-dependent protease calpain remain only partly understood. The -and m-calpains consist of a -or m-80-kDa large subunit (genes Capn1 and Capn2), and a common 28-kDa small subunit (Capn4). To assess the role of calpain in migration, we used fibroblasts obtained from Capn4 ؊/؊ mouse embryos. The cells lacked calpain activity on casein zymography and did not generate the characteristic calpain-generated spectrin breakdown product that is observed in wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
185
1
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(204 citation statements)
references
References 50 publications
17
185
1
1
Order By: Relevance
“…Indeed, Zaidel-Bar , 2007 et al recent studies have demonstrated that the calpain family has a regulatory function in cell motility, partly through the capacity to down regulate integrin-mediated adhesion complexes ( ; ; ; ). In that Glading , 2000et al Dourdin , 2001et al Bhatt , 2002et al Glading , 2002 context, talin seems to be one of major target of calpain leading to a rate-limiting step critical for FA disassembly ( ). It Franco , 2004 et al has also been shown that the expression of a calpain-resistent cortactin impaired cell migration and increased transient membrane…”
Section: Disassembly Of Cell-matrix Adhesionsmentioning
confidence: 99%
“…Indeed, Zaidel-Bar , 2007 et al recent studies have demonstrated that the calpain family has a regulatory function in cell motility, partly through the capacity to down regulate integrin-mediated adhesion complexes ( ; ; ; ). In that Glading , 2000et al Dourdin , 2001et al Bhatt , 2002et al Glading , 2002 context, talin seems to be one of major target of calpain leading to a rate-limiting step critical for FA disassembly ( ). It Franco , 2004 et al has also been shown that the expression of a calpain-resistent cortactin impaired cell migration and increased transient membrane…”
Section: Disassembly Of Cell-matrix Adhesionsmentioning
confidence: 99%
“…Thus, microtubules may direct kinesin motors bound to disassembly factors to focal sites to promote adhesion turn over. The molecular nature of factors that are delivered to focal adhesions by microtubules have remained elusive [134,137,139] but might include the class of calcium activated proteases, calpains [140,141] (see below). Interestingly, Ezratty et.…”
Section: Microtubule and Endocytic Regulation Of Focal Adhesionsmentioning
confidence: 99%
“…One might speculate that proteolysis of FAK is a negative feedback event that prevents liberated FAK from destabilizing adjacent adhesions. However, it should be noted that calpain cleavage of FAK may be restricted to v-src-transformed cells [141,196].…”
Section: Regulation Of Focal Adhesions and Actin By Proteolysismentioning
confidence: 99%
“…26 To further assess the role played by calpain in NF-kB induction by C2 ceramide, we transiently transfected wild-type and Capn4À/À MEFs with a LUC expression plasmid driven by the human iNOS promoter, a target of NF-kB. After 24 h, C2 ceramide was added and LUC activity was measured 4 and 8 h later.…”
Section: Capn4à/à Mefs Are Defective In Nf-jb Regulation By C2 Ceramidementioning
confidence: 99%
“…Calpains constitute a large family of cytosolic calciumdependent proteases which play an important role in the regulation of intracellular activities including cell spreading and migration, 25,26 myoblast fusion, programmed cell death and cell cycle progression. 27 The ubiquitous calpains, Calpain I (micro-calpain) and II (milli-calpain), consist of a large 80 kDa subunit encoded by the Capn1 and Capn2 genes, respectively, and a common 28 kDa small subunit encoded by Capn4.…”
Section: Introductionmentioning
confidence: 99%